Guidelines for Developing Organizational Citizenship Behaviors of Teachers Under Nakhon Ratchasima Primary Educational Service Area Office 7 - Poohongkaew , Teerapong; Phoojomjit, Pongphop (Journal for Developing the Social and Community, 2023)
The purposes this research were to 1) study the current conditions, desirable condition and need assessment of developing organizational citizenship behaviors of teachers under Nakhon Ratchasima primary educational service area office 7. 2) to study the guidelines for developing organizational citizenship behaviors of teachers under Nakhon Ratchasima primary educational service area office 7. The research was divided into 2 phases: Phase 1 study the current conditions, desirable condition and need assessment of study the current conditions, desirable condition and need assessment of developing organizational citizenship behaviors of teachers. The sample group were 336 school administrators and teachers. The research instrument were questionnaires reliability of .88, discrimination was 0.34–0.78. The statistics used for data analysis were mean and deviation standard. Phase 2: study the guidelines for developing organizational citizenship behaviors of teachers. The target groups include 5 school administrators and teachers for visiting best practices of organizational citizenship behaviors and 9 experts for assess suitability possibility of guideline. The research instrument were interview form and assessment form of guidelines. The results of the research were as follows: 1. The current state and the desirable state in overall was in the high level. The need assessment rank from high to low level was 1) civic virtue 2) sportsmanship 3) courtesy 4) altruism 5) conscientiousness 2. Guidelines for the development behavior of teachers of organizational citizenship, Include, 3 guidelines to civic virtue, 3 guidelines to sportsmanship, 3 guidelines to courtesy, 3 guidelines to altruism and 2 3 guidelines to conscientiousness. Evaluation, feasibility and utility was the highest in overall.